A comparison of bacterial communities from OMZ sediments in the Arabian Sea and the Bay of Bengal reveals major differences in nitrogen turnover and carbon recycling potential. Issue 8 (20th October 2020) - Lincy, Jovitha; Manohar, Cathrine Sumathi
ABSTRACT: The Northern Indian Ocean hosts two Oxygen Minimum Zones (OMZ), one in the Arabian Sea and the other in the Bay of Bengal. 16S rRNA gene amplicon sequencing was used to understand the total bacterial diversity in, the surface sediment off Goa within the OMZ of the Arabian Sea, and off Paradeep within the OMZ of the Bay of Bengal. Functional profiling was carried out to pinpoint the occurrence of specific bacterial operational taxonomic units (OTUs) which have been previously described to harbour certain genes/enzymes relevant to biogeochemical cycling of carbon, nitrogen, and sulfur compounds. The dominant phyla identified included Firmicutes (33.08%) and Proteobacteria (32.59%) from the Arabian Sea, and Proteobacteria (52.65%) and Planctomycetes (9.36%) from the Bay of Bengal. Only 30% of OTUs were shared between the sites which make up three-fourth of the Bay of Bengal OMZ bacterial community, but only one-fourth of the Arabian Sea OMZ sediment bacterial community. Statistical analysis indicated the bacterial diversity from sediments of the Bay of Bengal OMZ is ∼48% higher than the Arabian Sea OMZ. The community analysis combined with a predictive functional profiling of 16S rRNA amplicons revealed some major differences regarding sediment nitrogen fixation and carbon recycling, and identified a distinct bacterial community structure within the two shallow OMZ sites lying in the east coast and west coast of the peninsular India.